Devic's disease. - Peixoto, Irina; Ermida, Vera; Torres, Ana; Aparício, Maria Inês; André, Rui; Caldas, Jorge (Acta Médica Portuguesa, 2010)
Devic's disease, also known as Neuromyelitis Optica, is a demyelinating disease of the central nervous system, with selective involvement of the spinal cord and optic nerves. The authors describe a clinical case of acute myelitis, initially approached in the context of a nonspecific syndrome gripal, with subsequently sudden bilateral amaurosis, which leads to the diagnosis hypotesis of Devic's disease, a disease with poor prognosis in optic-spinal function and adequate symptomatic treatment.